Strategic Location of Satellite Salt Facilities for Roadway Snow and Ice Control. Issue 1 (January 2015) - Sullivan, James L.; Dowds, Jonathan; Novak, David C.; Scott, Darren M.
Roadway snow and ice control (RSIC) operations can account for as much as 10% of the annual budget of a state's department of transportation (DOT) in the snowbelt of the United States. Important considerations for planning RSIC operations are the locations and quantities of surface treatment materials. This study examined the use of satellite salt facilities (SSFs) and developed a novel, real-world approach for locating SSFs. The paper demonstrates a method for ranking the effectiveness of individual SSFs in their reduction of the distance that vehicles must travel to reload salt. The approach is demonstrated with the federal aid roadway network for the state of Vermont, and a locally optimal SSF location is identified for each of the existing service territories in the state. The results of an informal survey of satellite salt-siting practices among snowbelt DOTs are also reported. A critical aspect to siting new SSFs is the ability to use existing right-of-way around Interstates; survey respondents noted the need to explore public–private partnerships with landowners adjacent to the state highway right-of-way who may be willing to sell or lease small portions of cleared land for use as SSFs. From the survey information, the study compared a smaller set of ready-to-use SSF locations (with adequate right-of-way) with the locally optimized SSF locations.